DEVELOPMENT OF ICT FOCUSED TO THE QUALITY OF EDUCATION - SZŐKÖL, Štefan (Trends in education, 2008)
The trends of the development of the ICT usage and the communication of people via computers determine also the ways of there teaching. The goal of this work is to demonstrate the importance of information and communication technologies in the educational process as one of the most important tools enhancing the quality of education. The aim of education will shift to improve the skill of learning, critical thinking of the learner, improve the ability to communicate and use information and communication technologies as well as gathering, analyzing and using information effectively and efficiently.
Keywords: computer literacy; Quality of Education; ICT.